Emotional impact of Alzheimer's disease on the patient's family and how the diagnosis affects daily activities: integrative review (Research, Society and Development, 2022)
The choice of the population of family caregivers of elderly people with AD is of great relevance because this is a neurodegenerative disease that most occurs in the elderly population (60-70%), the growth of the elderly population in Brazil is noticeable, and along with it, the growth of diseases that affect the elderly, therefore, not only the health of that patient is important, but also the demand of caregivers with impacted mental (and physical) health. The present study aims to understand the greatest family impact after the diagnosis of Alzheimer's in the elderly due to the change in the family environment. This is an integrative literature review carried out through electronic searches in the following databases: National Library of Medicine (PUBMED), Virtual Health Library (BVS/MEDLINE) and ScienceDirect. In this study, the following descriptors were applied together with the Boolean operator AND: Alzheimer's disease and family caregiver and Alzheimer's disease and family relationship The guiding question to guide the search for articles was “What is the emotional impact of the Alzheimer's diagnosis on family and family relationships? How does it affect the mental health of the family caregiver?”. The total sample of this study consisted of 16 articles, which were characterized according to the authors, year, type of study, objective and results. Most of the included studies were published in the year 2020, in English and Portuguese. It is concluded that the task of caring can promote the development of morbidities, such as anxiety, depression, chronic stress and anguish. The intense coexistence with the patient is permeated by stressful situations that gradually increase the caregiver's burden and may present even more family conflicts.